Effective treatment of spacer tube reverse osmosis membrane concentrated leachate from an incineration power plant using coagulation coupled with electrochemical treatment processes. (April 2020) - Ren, Xu; Song, Kai; Xiao, Yu; Zong, Shaoyan; Liu, Dan
Abstract: Membrane concentrated leachate is an important secondary pollutant in incineration plants and needs to be treated properly in order to achieve the "zero discharge" standard for pollutants from incineration plants. In this study, coagulation followed by the electro-oxidation (EO), and electro-coagulation (EC) methods were studied. Each of these processes was used to treat the spacer tube reverse osmosis membrane concentrated leachate from an incineration plant. A single factor experiment was used to determine the optimal conditions for each individual process. In addition, a two-stage electrochemical treatment was investigated after combining the optimized EO and EC processes. The results showed that the two-stage electrochemical treatment process can achieve much higher removal efficiencies than when only EO or EC are applied. The optimal conditions for the two-stage electrochemical treatment process were 180 min of the optimized EO process as the 1st stage treatment process, followed by 60 min of the optimized EC process as the 2nd stage treatment process. After the optimized coagulation-EO-EC process, the total organic carbon (TOC), UV254, ammonia nitrogen (NH3 –N), total nitrogen (TN), color (CN), turbidity (TUB), and solution conductivity (SC) removal efficiencies were 96.19%, 98.98%, 96.54%, 88.21%, 99.72%, 98.24%, and 54.67%, respectively. This study can provide a theoretical basis for the treatment of concentrated leachate from MSW incineration plants. Highlights: Respectively determined the optimal conditions of coagulation, EO and EC process. Coagulation-EO-EC process is an effective method for treatment of sample. ＞90% of TOC, UV254 and NH3 –N were removed by optimal coagulation-EO-EC process. Coagulation-EO-EC process has the bright prospect of industrial application.